Decoding cellular communication: An information theoretic perspective on cytokine and endocrine signaling. (June 2022) - Schaper, Fred; Jetka, Tomasz; Dittrich, Anna
Abstract: Humoral communication is mediated by complex signaling pathways that are heterogeneously activated in individual cells. According to Shannon's information theory, these pathways can be interpreted as communication channels. Advanced single-cell analyses are used to understand reliable cellular communication in heterogenous cell populations. However, gaining knowledge from these complex measurements depends on appropriate evaluation methods. Due to their intuitive interpretation, flexibility and analytical power, information theoretic approaches are increasingly used to study cellular signaling. This review introduces the potential of the information theoretic measures channel capacity and mutual information for the interpretation of complex single-cell data and describes their practical application for the analysis of molecular mechanisms of endocrine and cytokine signaling. Highlights: Complex single-cell analyses open up insights into heterogenous cellular signaling. Shannon's information theory offers intuitive tools for analyzing signaling pathways. Mutual information determines the dependency between any two signaling events. Channel Capacity quantifies information transferred through signaling pathways. Advanced experiments and information theory decode biological information processing.